591 Sleep disturbances and executive function outcomes after critical care hospitalization in children with acquired brain injury. (3rd May 2021) - Williams, Cydni; Lim, Miranda; McEovy, Cindy; Hall, Trevor; Drury, Kurt; Shea, Steven
Abstract: Introduction: Annually, over 60, 000 children require critical care admission for acquired brain injury (ABI) in the US, and many face long-term cognitive morbidity. Over 50% of these children also develop sleep/wake disturbances (SWD). Given the importance of sleep to brain development and healing after injury, we hypothesized SWD in children after ABI would portend worse cognitive outcomes in domains of executive function. Methods: We performed a prospective observational study of N=80 children aged 6–18 years with ABI evaluated 1–3 months after critical care hospitalization. SWD were evaluated using the Sleep Disturbances Scale for Children (SDSC). The primary outcome was the Behavior Rating Inventory of Executive Function, 2nd Edition (BRIEF-2) Global Executive Composite (GEC; an age and gender adjusted T-score). Secondary cognitive outcomes included age adjusted scaled scores (ss) from the Delis Kaplan Executive Function System (DKEFS), Wechsler Intelligence Scale for Children, 5th Edition (WISC-V), and Children's Memory Scale (CMS). Relationships between the SDSC and cognitive measures were evaluated using Spearman correlation (rs). Multiple linear regression evaluated associations between SWD and GEC T-scores controlling for patient and ABI characteristics. Results: Sixty-five (81%) eligible children completed evaluation, and 48% had clinically significant SWD (total SDSC ≥39). Significant correlation (p<0.05) was found between the SDSC total score and worse GEC T-score (rs=0.60), and worse ss for CMS numbers forward (rs= -0.39), WISC-V coding (rs=-0.36), DKEFS number letter switching total time (rs=-0.38), and DKEFS category fluency (rs=-0.43). Presence of SWD was significantly associated with a full standard deviation worsening in the GEC T-score (β-coefficient= 10.2, 95% Confidence Interval=1.0–19.3) when controlling for age, race, gender, admission Glasgow Coma Scale, critical care intervention, and chronic comorbidities. Conclusion: Children with ABI requiring critical care have high rates of SWD after discharge that are associated with significantly worse executive function outcomes in overall function (BRIEF-2 GEC) and direct objective assessments (DKEFS, WISC-V, CMS) evaluating aspects of executive functioning including attention, processing speed, cognitive flexibility, and working memory. SWD may serve as a modifiable target to improve cognitive outcomes in this vulnerable pediatric population. Support (if any): This work is supported by the National Heart Lung and Blood Institute (K23HL150229-01)